2017
DOI: 10.1016/j.neuropsychologia.2017.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Is “Learning” episodic memory? Distinct cognitive and neuroanatomic correlates of immediate recall during learning trials in neurologically normal aging and neurodegenerative cohorts

Abstract: Although commonly interpreted as a marker of episodic memory during neuropsychological exams, relatively little is known regarding the neurobehavior of “total learning” immediate recall scores. Medial temporal lobes are clearly associated with delayed recall performances, yet immediate recall may necessitate networks beyond traditional episodic memory. We aimed to operationalize cognitive and neuroanatomic correlates of total immediate recall in several aging syndromes. Demographically-matched neurologically n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 65 publications
2
21
0
Order By: Relevance
“…This type of autonoetic strategy did not emerge as a regularly used strategy in our results, leading to the conclusion that the RAVLT seems unable to assess episodic memory to a reasonable degree, which is similar to the conclusion reached by previous authors (Tulving, 1985(Tulving, , 2002Van der Linden, 2004;Desgranges and Eustache, 2011). Consistent with Gavett and Horwitz's assertion that list-learning test interpretation lacks the construct validity to allowed unbiased estimates of episodic memory ability (Gavett and Horwitz, 2012), our results supplement those reported by Casaletto et al (2017), who focused on total immediate recall performance during learning trials and concluded that interpreting learning scores as equivalent to episodic memory may be erroneous. To avoid any confusion regarding the purpose of the RAVLT, and considering its widespread use, we encourage the use of simple terminology, i.e., "(supraspan) verbal memory, " to briefly characterize the RAVLT assessment.…”
Section: Discussionsupporting
confidence: 91%
“…This type of autonoetic strategy did not emerge as a regularly used strategy in our results, leading to the conclusion that the RAVLT seems unable to assess episodic memory to a reasonable degree, which is similar to the conclusion reached by previous authors (Tulving, 1985(Tulving, , 2002Van der Linden, 2004;Desgranges and Eustache, 2011). Consistent with Gavett and Horwitz's assertion that list-learning test interpretation lacks the construct validity to allowed unbiased estimates of episodic memory ability (Gavett and Horwitz, 2012), our results supplement those reported by Casaletto et al (2017), who focused on total immediate recall performance during learning trials and concluded that interpreting learning scores as equivalent to episodic memory may be erroneous. To avoid any confusion regarding the purpose of the RAVLT, and considering its widespread use, we encourage the use of simple terminology, i.e., "(supraspan) verbal memory, " to briefly characterize the RAVLT assessment.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, numerous studies suggested that severe amnesia could be observed in patients with non-AD or mixed AD pathology, such as DLB (Kraybill et al, 2005;Yoshizawa et al, 2013;Salmon et al, 2015), FTLD (Elgren et al, 1993;Grahan et al, 2005;, or to a lesser degree VaD (Jicha et al, 2006;Reed et al, 2007). This last decade, memory impairment was reported in clinicallydefined DLB (Petrova et al, 2015;Molano et al, 2010), in the clinical subtypes of FTLD such as behavioural variant frontotemporal dementia (Hornberger et al, 2010;Bertoux et al, 2014), semantic progressive aphasia (Casaletto et al, 2017), non-fluent progressive aphasia (Ramanan et al, 2016), amyotrophic lateral sclerosis (Mantovan et al, 2003), progressive supranuclear palsy (Kobylecki et al, 2015) as well as in clinically-defined VaD (Mathias & Burke, 2009) although inconsistent findings were reported in this disease due to the variable topography of vascular lesions. Not least of all, severe amnesia is also the main feature of hippocampal sclerosis, often related to aberrant TDP-43 immunohistochemistry (Nelson et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Table 2 for the specific measures included per domain. The selected neuropsychological measures have been widely published and shown to be sensitive to age-related neurologic processes [28]. For domains with more than one measure, scores were blom rank transformed to achieve normality before conversion into sample-based z-scores.…”
Section: Neuropsychological Measuresmentioning
confidence: 99%